Comprehensive Evaluation of the Current Knowledge on Breast Implant Associated-Anaplastic Large Cell Lymphoma - Yoo, Hyokyung; Park, Ji-Ung; Chang, Hak (Archives of Plastic Surgery, 2022)
Breast implant-associated anaplastic large cell lymphoma (BIA-ALCL) is a recently spotlighted T-cell origin non-Hodgkin's lymphoma with an increasing incidence of over 800 cases and 33 deaths reported worldwide. Development of BIA-ALCL is likely a complex process involving many factors, such as the textured implant surface, bacterial biofilm growth, immune response, and patient genetics. As the incidence of BIA-ALCL is expected to increase, it is important for all surgeons and physicians to be aware of this disease entity and acquire thorough knowledge of current evidence-based guidelines and recommendations. Early detection, accurate diagnosis, and appropriate treatment are the foundations of current care.
Keywords: BIA-ALCL; breast implants; biofilm; immunity; genetics